O uso de peixes em estudos experimentais ecotoxicológicos "in situ", avaliando os efeitos da poluição aquática urbana em reservatórios - Luis Alberto Saenz Isla (2016)
Experimental studies ecotoxicological in situ are used to demonstrate the effectiveness of using fish as an environmental assessment tool in biomonitoring programs. In this thesis are shown researches and concepts of how the fish are used as organisms "sentinels", expressing the degree of exposure and toxicity of anthropogenic pollutants on these organisms and the impact they can generate on human health. It also emphasizes the impact of urban pollution on natural and artificial aquatic ecosystems. To demonstrate it, this thesis was divided into the following chapters: Chapter 1 - Fish: sentinels of environmental monitoring?, this section show some important ecotoxicologic concepts to the development of in situ experiments of environmental assessment Chapter 2 - Use of Nile Tilapia (Oreochromis niloticus) as bioindicator of aquatic pollution in two reservoirs in Itabapoana River, Rio de Janeiro, Brazil, that consist in an in situ experiments using biochemical biomarkers in tilapias exposed by short time periods to natural environmental conditions in hydroelectric reservoirs. Chapter 3 - Bioaccumulation of metals lead and zinc in fishes during the Ecotoxicologic Biomonitoring Programm in the Pampulha Reservoir, Belo Horizonte (MG-Brazil), this part of the thesis present an in situ experiment carried out in the Pampulha Reservoir to determine if there is bioaccumulation of heavy metals in tilapia tissues during a dredging operations in the reservoir. The results evidenced that the fish are great sentinels organisms, and can be used in environmental biomonitoring programs for aquatic ecosystems.